The effects of crowd logistics capabilities on crowd logistics performance moderated by supply chain uncertainty and risk in malaysia logistics industry - Nor Rokiah Hanum, Md Haron (2024)
The emerging trend of crowd logistics in e-commerce has bloomed in recent years. Crowd logistics has been considered as an innovative solution to solve the last-mile delivery problems. However, there were still unclear indicators and a lack of empirical evidence on logistics performance measurement, specifically from the crowd logistics perspective. This quantitative research design used a survey questionnaire as the instrument for this study. A pre-test was completed before distributing the cross-sectional web-based survey questionnaire among the crowd logistics companies in Malaysia. From 247 population in crowd logistics companies, a minimum sample size of 146 were gathered. Using a simple random sampling, this research collected 164 responses from the data collection, which equal to 66% of response rate. This study aimed to investigate the relationship between crowd logistics technological capabilities (CLTC), crowd logistics organizational logistics capabilities (CLOC), crowd logistics environmental capabilities (CLEC), and a moderating role of supply chain uncertainty and risk (SCUR) towards the crowd logistics performance (CLP) in Malaysia. The integration using a Resource-based View (RBV), Technology-Organization-Environment (TOE) framework, and Contingency Theory was adapted to discover the ability and influence of crowd logistics capabilities and crowd logistics performance. The result indicated that logistics resource match capability and delivery capability strengthen crowd logistics performance. While platform ease of use, logistics agility, innovation capability, customer response capability, traffic and congestion and waste management do not strengthen crowd logistics performance. The effect of supply chain uncertainty and risks towards platform ease of use and crowd logistics performance was strengthened when the SCUR was implemented. Practically, the study can be a guideline for practitioners in managing the crowd logistics environment to ensure continuous improvement in crowd logistics performance in organizations. This research highlights the importance of crowd logistics performance. It shows that crowd logistics capabilities could impact crowd logistics performance and, at the same time, can provide strategic measurement toward achieving sustainability in crowd logistics performance.